2023
DOI: 10.1111/radm.12573
|View full text |Cite
|
Sign up to set email alerts
|

Boundary organisations in regional innovation systems: traversing knowledge boundaries for industry 4.0 regional transformations

Abstract: In this article, we explore and theorise how actors in the Sheffield City Region envision the development and orchestration of an innovation ecosystem in order to capture value from industry 4.0 technologies for manufacturing firms. This is theoretically motivated by the need to harmonise the knowledge combination and recombination practices that are required for the successful existence of innovation ecosystems at a regional level, in the applied context of industry 4.0 regional transformations. Drawing on da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 127 publications
(190 reference statements)
0
1
0
Order By: Relevance
“…This infrastructure has a human part and a strictly material part; however, both refer to the generation, development and dissemination of new scientifictechnological knowledge [70]. A crucial point is having a research and development structure and facilities, and access to networks and financing [71]. In addition, it has been shown that maintaining a link and interaction with the institutions that carry out research has important benefits [72].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This infrastructure has a human part and a strictly material part; however, both refer to the generation, development and dissemination of new scientifictechnological knowledge [70]. A crucial point is having a research and development structure and facilities, and access to networks and financing [71]. In addition, it has been shown that maintaining a link and interaction with the institutions that carry out research has important benefits [72].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, education and training in emerging technologies has proven to be a good strategy, and at the same time the design of initiatives that encourage change in consumer behavior will be increasingly important [21,71,81], especially for small producers who find it more difficult to access this type of technology, and this could cause greater asymmetries in the different agri-food regions. Lastly, it is important to directly link financial and nonfinancial instruments such as supply and demand incentives, fiscal incentives, economic incentives and subsidies [71,90], facilitate policy making, and provide public services such as the Internet [81].…”
Section: Discussionmentioning
confidence: 99%
“…The automotive sector has been significantly transformed by the implementation of lean production concepts, serving as a prominent illustration of the harmonious coexistence of sustainability and efficiency. The primary objective of lean manufacturing is to effectively reduce waste, encompassing several aspects such as surplus materials, time, and labour [25]- [29]. In recent years, there has been a notable increase in the use of sustainable packaging solutions due to the global concern regarding the detrimental impact of excessive packaging waste on the environment.…”
Section: Case Studies In Sustainable Transformationmentioning
confidence: 99%
“…On a more positive note, SMEs may play a positive role in the recovery of the global economy as key providers of many essential goods and services (Deng and Zhang, 2018; Matsuzaki et al., 2021), using their agility to navigate through major economic crises (Kottika et al., 2020). Thus, we need to identify and understand the factors that may help SMEs use technological innovations to not only recover from economic downturn but also improve their long‐term productivity and capabilities (Petruzzelli et al., 2022; Martins and Singh, 2023).…”
Section: Introductionmentioning
confidence: 99%